Synthesis, characterisation and some chemistry of C- and B-substituted carboxylic acids of cobalt bis(dicarbollide) - Nekvinda, Jan; Šícha, Václav; Hnyk, Drahomír; Grüner, Bohumír (Dalton transactions (Cambridge, England, 2014)
Low temperature reactions of lithiated cobalt bis(1,2-dicarbollide)(1-) (1⁻) in DME with carbon dioxide leads to the substitution of 1⁻ at the C-atoms by carboxy function(s). This results in a good yield formation of monosubstituted and disubstituted products of formulations [(1-HOOC-1,2-C2B9H10)(1',2'-C2B9H11)-3,3'-Co)](-) (2⁻) and [(HOOC)2-(1,2-C2B9H10)2-3,3'-Co](-) (3a,b⁻), respectively. Indeed, the latter compound is in fact a mixture of two diastereoisomers, denoted here as 1,1'-anti (3a⁻) and 1,2'-syn-isomer (3b⁻), from which only the former major species (3a⁻) could be isolated in pure form. Considerations about stereochemistry of these species are supported by geometry optimizations and calculations of (11)B NMR shifts at the GIAO-DFT level. In addition, three monocarboxylic acids with three different linear spacers between the carboxy groups and the cage are reported. The first one of the formula [(1-HOOC-CH2-1,2-C2B9H10)(1',2'-C2B9H11)-3,3'-Co](-) (5⁻) results in a lithiation followed by reaction with BrCH2COOEt and hydrolysis of the respective ethyl ester (4⁻). Another one with ethylene chain [(1-HOOC-(CH2)2-1,2-C2B9H10)(1',2'-C2B9H11)-3,3'-Co](-) (6⁻) was prepared by the oxidation of a hydroxypropyl derivative of the ion 1⁻. The sole representative of B-substituted species of the formulation [8-(HOOC-CH2-O-1,2-C2B9H10)(1',2'-C2B9H11)-3,3'-Co](-) (7⁻) is prepared by alkylation of the known 8-hydroxy derivatives of the ion 1⁻ by BrCH2COOEt and alkaline hydrolysis. A synthetic route to active nitrofenyl esters (8⁻, 9⁻ and 10⁻) is described here based on the respective acids 5⁻ to 7⁻. As verified, the nitrophenyl esters provide easy access to the formation of amidic bonds between the boron cage and organic primary amino functions. Examples of compounds containing butylamide or benzylamide [(1-RNHOC-(CH2)n-1,2-C2B9H10)(1',2'-C2B9H11)-3,3'-Co](-) (n = 1,2; R = Bu 11a,b⁻, R = Bn: 12a,b⁻) end group are described. Also the possibility of inter-connecting two clusters of the anion 1⁻ via the amidic bond is shown in derivative (13⁻). These methods are applicable in the synthesis of a variety of functional molecules, particularly those applicable in drug design, surface modifications, and material science.